Enforceable Contracts under Generalized Information of the Court - Francesco Squintani (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
Bernheim and Whinston (1997) (henceforth BW) formalize court's verifiability as a correspondence mapping actually played actions into events (i.e. sets of actions) verified by the court. Their normal-form analysis restricts attention to partitional product correspondences. They define any element in the partition a "complete" enforceable contract. After motivating the discussion of non-partitional and non-product correspondences by means of simple examples, we show that the BW approach may fail to capture all feasible outcomes for product non-partitional correspondences, and that is valid against all partitional non-product ones only if one allows for a joint liability regime. Even in the case of joint liability regimes, the BW approach may be extended only to deal with non-product or non-partitional correspondences. Therefore, a definition of enforceable contract that is independent of the players' payoffs may not capture all feasible outcomes.
Keywords: 330